Legal Aspects of Collaborative Programs in Integrated Waste Management Systems : Regulatory Perspective in Batam City - Riza Rosalya; Rahadi Pratama; Fadlan Fadlan (International Journal of Humanities and Social Sciences Reviews, 2025)
This research examines the legal aspects of collaborative programs in integrated waste management systems in Batam City. The study focuses on analyzing the regulatory framework, identifying implementation challenges, and developing recommendations for effective multi-stakeholder collaboration. Using a mixed normative and empirical juridical approach, data was collected through document analysis, in-depth interviews, and field observations. The findings reveal significant regulatory fragmentation between central and local governments, coordination gaps among stakeholders, and legal barriers in public-private partnerships. The research proposes improvements to the legal framework, strengthening coordination mechanisms, and developing supportive legal instruments. The study contributes to understanding how regulatory frameworks can better facilitate collaborative waste management programs in urban settings.